(3GdaQGFV GdSLGhfOjIs - (3GdSLGhfOj, eMeO Hf eMehO Hf YHO GdQTjO, J (B596 (3g`s ((3YeQ Hf SfGfs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg MeO GdTGcQjf bGd QShd Gddg Udi Gddg Ydjg hSde JYdehG GdaQGjV hYdehgG GdfGS aEfgG fUa GdYdes
(3BNQgG (B:s
(3hbGd Ydj hGHf eSYhO QVj Gddg YfgeG jQK HYVge ef HYV EdG eeG hQK cd hGMO efge ef eGd UGMHgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 27s
(3eYLe GdeDdajf (B3 / 652s
(3cTa GdXfhf (B2 / 1247s
(3gOjI GdYGQajf (B2 / 106s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdaQGFVs